Analysis Of Rev1p And Pol ζ In Mitochondrial Mutagenesis Suggests An Alternative Pathway Of Damage Tolerance - Kalifa, Lidza (2007)
Ultraviolet light is a potent DNA damaging agent that induces bulky lesions in DNA which block the replicative polymerases. In order to ensure continued DNA replication and cell viability, specialized translesion polymerases bypass these lesions at the expense of introducing mutations in the nascent DNA strand. A recent study has shown that the N-terminal sequences of the nuclear translesion polymerases Rev1p and Pol ζ can direct GFP to the mitochondrial compartment of Saccharomyces cerevisiae. We have investigated the role of these polymerases in mitochondrial mutagenesis. Our analysis of mitochondrial DNA point mutations, microsatellite instability, and the spectra of mitochondrial mutations indicate that these translesion polymerases function in a less mutagenic pathway in the mitochondrial compartment than they do in the nucleus. Mitochondrial phenotypes resulting from the loss of Rev1p and Pol ζ suggest that although these polymerases are responsible for the majority of mitochondrial frameshift mutations, they do not greatly contribute to mitochondrial DNA point mutations. Analysis of spontaneous mitochondrial DNA point mutations suggests that Pol ζ may play a role in general mitochondrial DNA maintenance. In addition, we observe a 20-fold increase in UV-induced mitochondrial DNA point mutations in rev deficient strains. Our data provides evidence for an alternative damage tolerance pathway that is specific to the mitochondrial compartment.